The SMART university: the transformational role of learning analytics. Issue 12 (12th November 2018) - Lewis, David Jonathan Arwel
Abstract : Purpose: This paper aims to answer the following questions: What is the process and policy journey that a university must go through in implementing an effective learning analytics programme? What are the drivers for undertaking such an activity, and who are the stakeholders? Design/methodology/approach: The journey of the information, the process or the stakeholder is placed at the heart of the programme, so a primarily ethnographic methodology is appropriate, although ultimately the outcomes of analytics are usually quantitative. Findings: In undertaking the journey to a full implementation of an analytics programme, a university must clearly know the strategic driver for starting, and the clear outcomes, if a purposeful path is to travelled. Originality/value: As a currently growing area of interest for lots of higher and further education institutions in the UK and worldwide, learning analytics should be high on everyone's agenda. This viewpoint is intended to provide a short overview to the process and the important strategic drivers.